Actividad antimicótica del extracto etanólico de hojas de Annona Reticulata L. (chirimoya roja) frente a Candida albicans ATCC 10231 - Yuimachi Tapullima, Meysonier (2022)
The research is basic and exploratory with an experimental, prospective and cross-sectional design. The objective of the research is to evaluate the antifungal activity of the ethanolic extract of Annona reticulata L. (red custard apple) leaves against Candida albicans ATCC 10231, the population consisted of Annona reticulata L. (red custard apple) plants, solubility tests, identification of secondary metabolites and the antifungal activity of the ethanolic extract at concentrations of 25 %, 50 %, 75 % and 100 % against Candida albicans ATCC 10231 were carried out. The presence of phenolic compounds, tannins, flavonoids and alkaloids could be evidenced, finally no antifungal activity was evidenced, reporting inhibition halos of 6 mm of the same size as the negative control of distilled water